Glycoside scutellarin enhanced CD-MOF anchoring for laryngeal delivery - Kena Zhao; Tao Guo; Caifen Wang; Yong Zhou; Ting Xiong; Li Wu; Xue Li; Priyanka Mittal; Senlin Shi; Ruxandra Gref; Jiwen Zhang (Elsevier, 2020)
It is essential to develop new carriers for laryngeal drug delivery in light of the lack of therapy in laryngeal related diseases. When the inhalable micron-sized crystals of γ-cyclodextrin metal-organic framework (CD-MOF) was utilized as dry powder inhalers (DPIs) carrier with high fine particle fraction (FPF), it was found in this research that the encapsulation of a glycoside compound, namely, scutellarin (SCU) in CD-MOF could significantly enhance its laryngeal deposition. Firstly, SCU loading into CD-MOF was optimized by incubation. Then, a series of characterizations were carried out to elucidate the mechanisms of drug loading. Finally, the laryngeal deposition rate of CD-MOF was 57.72 ± 2.19% improved by SCU, about two times higher than that of CD-MOF, when it was determined by Next Generation Impactor (NGI) at 65 L/min. As a proof of concept, pharyngolaryngitis therapeutic agent dexamethasone (DEX) had improved laryngeal deposition after being co-encapsulated with SCU in CD-MOF. The molecular simulation demonstrated the configuration of SCU in CD-MOF and its contribution to the free energy of the SCU@CD-MOF, which defined the enhanced laryngeal anchoring. In conclusion, the glycosides-like SCU could effectively enhance the anchoring of CD-MOF particles to the larynx to facilitate the treatment of laryngeal diseases.